Campaigns. (Ecologist)
Provides information on the plight of the indigenous people in South America's Mato Grosso Pantanal. How farmers in India are seeking ways to get Kentucky Fried Chicken to leave; Information on the construction of the Ralco Dam in Chile by the ENDESA Company. INSET: In brief..